Technology of Structural Optimization for Subsidiary in Enterprise Information Systems - Saif Q. Muhamed; Mohammed, Mohammed Q.; Nayl, Th.; Mikhnov, D.; Mikhnova, A. (My University, 2019)
This article demonstrates the development of structure optimization technology for technical means of subsystems designed for solving susidiary problems in information and control system of an arbitrary enterprise. This technology based on modification of existing technology on structure optimization for technical registration of enterprise energy resources. Changes in the technology steps are mainly stipulated by constant enhancement and improvement of technical characteristics of wireless networks. Secondly, it is stipulated by emerging of sensors with custom interfaces for acquiring and measuring physical values, consequently enabling interaction with different networks, as well as emerging of a wide spectrum of interface converters. Дана стаття демонструє розвиток технології оптимізації структури технічних засобів підсистем, призначених для рішення задач в інформаційно-управляючій системі довільного підприємства. Дана технологія заснована на модифікації існуючої технології оптимізації структури для технічної реєстрації енергоресурсів підприємства. Зміни в технологічних кроках в основному обумовлені постійним вдосконаленням технічних характеристик бездротових мереж. По-друге, це зумовлено появою сенсорів з індивідуальними інтерфейсами для придбання та вимірювання фізичних величин, що дозволяє взаємодіяти з різними мережами, а також формувати широкий спектр інтерфейсних перетворювачів.
Keywords: Sensor; Wireless Network; Control Point; Optimization